Penerapan Model Inquiry Lesson Terhadap Habits Of Mind Peserta Didik Kelas X MIPA Pada Materi Ekosistem: (Application of the Inquiry Lesson Model to the Habits of Mind of Class X Mathematics and Natural Sciences Students on Ecosystem Materials) - Kusumawati Pertiwi Wiwi; Sistiana Windyariani; Setiono Setiono (BIODIK, 2022)
This study aims to see how the habits of mind of students with the application of the inquiry lesson learning model. Inquiry lesson is one of the stages of Levels of Inquiry (LoI) Wenning (2010). Using the Pre-experimental method. with One Group Posttest only design. Habits of mind according to Costa and Kallick (2012) which consists of 16 indicators. This research was conducted at SMA Negeri 01 Cigombong Bogor class X MIPA 5 academic year 2021/2022 in the subject of Ecosystem Biology. The research instrument used was the Habits of mind questionnaire which consisted of 43 statements given after the learning process with the inquiry lesson. The results showed that the application of the inquiry lesson model had a good influence on the habits of mind of students. It is proven in the acquisition of an n-gain score of 0.05, which means that there is a low increase, and the average percentage value per indicator is 76%. Key words: Inquiry lesson, application, habits of mind, ecosystem Â  ABSTRAK Penelitian ini bertujuan untuk melihat bagaimana habits of mind peserta didik dengan penerapan model pembelajaran inquiry lesson. Inquiry lesson merupakan salah satu tahapan dari Levels of Inquiry (LoI) Wenning (2010). Menggunakan metode Pra- eksperiment dengan desain One Group Postest only. Habits of mind yang digunakan menurut Costa dan Kallick (2012) yang terdiri dari 16 indikator. Penelitian ini dilakukan di SMA Negeri 01 Cigombong Bogor kelas X MIPA 5 tahun ajaran 2021/2022 pada mata pelajaran Biologi materi Ekosistem. Instrumen penelitian yang digunakan yaitu angket Habits of mind yang terdiri dari 43 pernyataan yang diberikan setelah proses pembelajaran dengan inquiry lesson. Hasil penelitian menunjukan bahwa penerapan model inquiry lesson memiliki pengaruh baik terhadap habits of mind peserta didik. Dibuktikan dalam perolehan skor n-gain sebesar 0,05 yang artinya terdapat peningkatan rendah, serta rata-rata nilai persentase per-indikator sebesar 76% . Kata kunci: Inquiry lesson, penerapan, habits of mind, ekosistem